Evaluasi Pemilihan Penyedia Jasa Truk Angkutan Barang Menggunakan Metode Simple Additive Weighting - Somadi, Somadi; Pasaribu, Desi Arista; Khoiriyah, Rizky (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This study aims to determine the priority of freight truck service providers at PT. XYZ by using the simple additive weighting method. Data collection techniques using interviews and documentation study. The criteria for selecting a freight trucking service provider uses the dimensions of the service marketing mix. Based on the results of the study that the freight truck service providers selected to be the first choice priority of the three existing service providers are Chess Prime Trans, followed by MGM Bosco Logistics as the second choice, and PT. Indo Partner Logistics as a third choice.